GAM (Generalized Additive Model) Analysis for Predicting Potential Area of Lemuru in Bali Strait - Semedi, Bambang; Hardoko, Hardoko; Dewi, Setya Nuri Fatma; Fatimah A., Putri Dila Nur (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2022)
Lemuru is a potential fish in the Bali strait with 80% of the total catch. The fishing process is determined by the efficiency and effectiveness of improving the fishing area. However, the lack of awareness of fishing areas by fishermen tend to be less optimal, waste of time and fuel. One of the alternatives is to use remote sensing data. Fishing areas information can be obtained through oceanographic parameters. Sea surface temperature and chlorophyll-a are main factor determined fishing areas. This study aims to predict the fishing area of S. lemuru using GAM (Generalized Additive Model) analysis, the results of this model can show a range of oceanographic factors that significantly explain high fishing related to marine environmental parameters. Fishing data and coordinates were obtained from PPP Muncar, Banyuwangi on May 2021. Data used is from fishing data around two years in Bali strait. The optimum value of chlorophyll-a Lemuru fishing is at 0.1- 1.2 mg m-3 and sea surface temperatures around 27 - 31°C. According to GAM statistical modelling, the most appropriate fishing area was data combination among data fishing, sea surface temperature of AIC and CDE AIC around 23044.21, and CDE 8.18%. The whole area of Bali strait is Lemuru fish distribution yet located in different areas each season such as west season at latitude (-8.26°)-(-8.59°) longitude (114.466°)-(114.449°), east season at latitude (-8.74°)-(-8.70°) longitude (114.299°)-(114.187°), while in transition season 1 at latitude (-8.50°)-(-8.78°) longitude (114.819°)-(115.070°) and season 2 at latitude (-8.27°)-(-8.56°) longitude (114.742°)-(114.819°